Fotometria CCD UBVRI de aglomerados de estrelas das Nuvens de Magalhães - Saurin, Tiago Abreu (2006)
We present UBVRI CCD photometry in the Johnson-Cousins photometric system for a sample of twenty nine Magellanic Cloud star clusters (Lindsay 16, 26, 29, 48, 53, 61, 66, 67, 72, 76, 79, 82, 83, 85 of the Small Cloud and NGC 1783, 1810, 1818, 1831, 1847, 1856, 1870, 1895, 2004, 2100, 2121, 2159, 2164, 2210, and [H60b] 11 of the Large Cloud) with a photometric calibration mean error less than 0.01 mag in the V band at a 66% confidence level. The coordinates of the center of symmetry for every cluster have been obtained, with a mean error less than 0.5′′, using an implementation of autocorrelation mirror algorithm proposed by Djorgovski (1988). The surface brightness profiles for every cluster have been obtained from CCD images in the V band and used to adjust the King (1962) and EFF (Elson et al., 1987) models. The structural parameters of the EFF model have been used to estimate the mass and luminosity for every cluster. The apparent integrated brightness in the V band, the U−B, B−V, V−R, and R−I colours, and an age calibration as function of effective colours (i.e., integrated colour at a radius where surface brightness reaches 20% of center value), (B−V)ef , (V−R)ef and (R−I)ef , are presented. The age versus effective colour calibration has been used to obtain an age estimation of (6.1±1.2)×107 years for the star cluster Lindsay 79. Finally, the data analisys in the present work is inconclusive regarding the existence or not of mass segregation in the clusters of our sample, particulary for NGC 1818, NGC 2004, and NGC 2100 objects indicated in the literature as having primordial mass segregation.